The Effectiveness of Learning Using the GBL Model to Improve Creativity and Islamic Education Learning Outcomes of Students at SMP ISLAM AS SURUUR - Qiqi Yulianti Zaqiah; Sarah Nofis A’raaf; Siti Rosyidah; Uswatun Hasanah; Rahman Agussalim (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to determine the effectiveness of using the Game-Based Learning (GBL) model in improving the creativity and learning outcomes of Islamic Religious Education (PAI) in students. The GBL model is a learning approach that integrates games in the learning process to achieve educational goals. This study uses an experimental method with a pretest-posttest design in two groups, namely the experimental group using GBL and the control group using conventional methods. The results show that the use of the GBL model can significantly increase students' creativity and learning outcomes compared to conventional methods. It is hoped that the results of this research can make a positive contribution to the development of innovative learning methods in the field of Islamic Religious Education.